Sejarah Nasional Indonesia - Marwati Juned Pusponegoro (Balai Pustaka, 1984)
ast jil.v =c.1/Oen, Jil.VI=c.1/oen, Jil.I=c.1-3; Jil.III=c.1/ast jil.IV=c.1-5 ; jil.V,c.2-3; jil.VI,c.2-4/ tr, jil. II=c.1-2/